Security and Trust in Mobile Interactions: A Study of Users' Perceptions and Reasoning - Sellen, Abigail (Proceedings of Ubicomp 2004, 2004)
This paper describes an investigation into the trust and security concerns of users who carry out interactions in ubiquitous and mobile computing environments. The study involved demonstrating an "electronic wallet" to pay for a meal in a simulated restaurant, and analyzing subjects' responses based on structured interviews. We asked the users to rankorder five payment methods including three choices for the payment target, and both wired and wireless connections. The analysis led us to classify the users into trust-, social- and convenience-oriented clusters. We provide a detailed analysis of the users' reasoning about trust-related issues, and draw conclusions about the design of secure interaction technologies for ubiquitous computing.